MANAJEMEN BUDAYA ORGANISASI MULTIKULTURAL DI PERUSAHAAN INDONESIA EMPIRIS - Ahmad Jet Alamin A; Margono; Heni A. Adilan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines the management of multicultural organizational culture in Indonesian companies within the context of globalization and free trade agreements. With its vast cultural diversity, Indonesia presents both challenges and opportunities for firms to enhance competitiveness by managing diversity more effectively. The research aims to analyze and evaluate multicultural organizational culture management practices, including the effects of free trade on organizational dynamics and structure, as well as the supporting and inhibiting factors influencing such management. The findings indicate that leaders must possess cultural awareness and strong communication skills to create an inclusive workplace environment. The study further recommends that both companies and the government formulate policies to support MSME development and implement efficient management strategies, enabling firms—particularly MSMEs—to maximize the benefits of free trade.